Bronchiectasis Exacerbations: The Role of Atypical Bacteria and Respiratory Syncytial Virus. Issue 3 (2015) - Metaxas, Eugenios I; Balis, Evangelos; Papaparaskevas, Joseph; Spanakis, Nicholas E; Tatsis, Georgios; Tsakris, Athanasios
Abstract : BACKGROUND: Aside from the known role of common bacteria, there is a paucity of data regarding the possible role of atypical bacteria and viruses in exacerbations of non-cystic fibrosis bronchiectasis. OBJECTIVE: To explore the possible role of atypical bacteria (namely, Mycoplasma pneumoniae and Chlamydophila pneumoniae ) and respiratory syncytial virus (RSV) as causative agents of bronchiectasis exacerbations. METHODS: A cohort of 33 patients was studied over a two-year period (one year follow-up for each patient). Polymerase chain reaction for the detection of M pneumoniae, C pneumoniae and RSV in bronchoalveolar lavage samples were performed during all visits. Antibody titres (immunoglobulin [Ig]M and IgG) against the aforementioned pathogens were also measured. In addition, cultures for common bacteria and mycobacteria were performed from the bronchoalveolar lavage samples. RESULTS: Fifteen patients experienced a total of 19 exacerbations during the study period. Although RSV was detected by polymerase chain reaction during stable visits in four patients, it was never detected during an exacerbation. M pneumoniae and C pneumoniae were never detected at stable visits or during exacerbations. IgM antibody titres for these three pathogens were negative in all patient visits. CONCLUSIONS: Atypical pathogens and RSV did not appear to be causative agents of bronchiectasis exacerbations.